2022
DOI: 10.3390/math10152794
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Athlete Signal Processing Methodology for Balance Control Ability Assessment with Multi-Headed Self-Attention Mechanism

Abstract: In different kinds of sports, the balance control ability plays an important role for every athlete. Therefore, coaches and athletes need accurate and efficient assessments of the balance control ability to improve the athletes’ training performance scientifically. With the fast growth of sport technology and training devices, intelligent and automatic assessment methods have been in high demand in the past years. This paper proposes a deep-learning-based method for a balance control ability assessment involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In addition, one study demonstrated that WT was appropriate for diseases connected to the identification and diagnosis of balance [ 19 ]. It has been discovered that WT can reveal the change in COP displacement that cannot be observed by conventional methods [ 29 , 30 , 31 ]. Studies have revealed that the increase in energy in the frequency band indicated that subjects were at risk of falling, which was similar to the results of this study, and the larger the WT, the worse the balance capability [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study demonstrated that WT was appropriate for diseases connected to the identification and diagnosis of balance [ 19 ]. It has been discovered that WT can reveal the change in COP displacement that cannot be observed by conventional methods [ 29 , 30 , 31 ]. Studies have revealed that the increase in energy in the frequency band indicated that subjects were at risk of falling, which was similar to the results of this study, and the larger the WT, the worse the balance capability [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental Transformer architecture comprises an input layer, multi-head self-attention blocks, normalization layers, feedforward layers, and residual connection layers. Essentially, it embodies an Encoder-Decoder framework [ 26 ]. Key components within the Transformer model are the multi-head self-attention mechanism and the autoencoder.…”
Section: Methodsmentioning
confidence: 99%
“…Lu et al [7] propose a deep learning-based method for a balance control ability assessment involving an analysis of the time-series signals from the athletes. The proposed method directly processes the raw data and provides the assessment results, with an endto-end structure.…”
mentioning
confidence: 99%